Maternal and Child Health Matters Around the World - Mohammadnezhad, Masoud; Huq, Nafisa; Mohammadnezhad, Masoud; Huq, Nafisa (IntechOpen, 2020)
This edited volume, (3z(BMaternal and Child Health Matters Around the World(3y(B, is a collection of reviewed and relevant research chapters, offering a comprehensive overview of recent developments in the field of medicine. The book comprises single chapters authored by various researchers and edited by an expert active in the medical research area. All chapters are complete in itself but united under a common research study topic. This publication aims at providing a thorough overview of the latest research efforts by international authors on maternal and child health matters around the world, and open new possible research paths for further novel developments.s
English
Keywords: Birth control, contraception, family planning; Health psychology